RANCANG BANGUN SISTEM PENGAMBILAN CITRA DAN PENGATUR POSISI JARAK OBYEK PADA MIKROSKOP DIGITAL MENGGUNAKAN JARINGAN WiFi SMARTPHONE ANDROID BERBASIS RASPBERRY Pi 3 DAN MIKROKONTROLER ESP32 - Putranto, Ari Bawono; Baital, Muhammad Sawal; Muhlisin, Zaenul; Adi, Kusworo (BERKALA FISIKA, 2020)
In  this  study,  the  ESP32  microcontroller  and  the  Raspberry  Pi  have  been  successfully combined  to  adjust  the  position  of  the  digital  microscope  object  and  take  images  using  an android smartphone-based application via a WiFi network. The working method of adjusting the position of the microscope object is done by using the number of steps on a unipolar stepper motor  starting  from  the  farthest  distance  to  the  digital  microscope  objective  lens  which  is regulated by the ESP 32 microcontroller. Meanwhile, viewing the microscope object directly can  be  done  via  a  mobile  screen  connected  to  a  WiFi  network  to  a  digital  microscope  USB camera that has been converted into an IP camera by the Raspberry Pi. Therefore, through the use of a digital microscope application with an Android smartphone, it will be easier to obtain a sample image of a digital microscope object when conducting experiments in the laboratory.Keywords: Digital Microscope, Android Smartphone, WiFi, Rsabperry Pi, Microcontroller ESP 32